Papanicolaou test in Brazil: analysis of the National Health Survey of 2013 and 2019 - Azevedo e Silva, Gulnar; Damacena, Giseli Nogueira; Ribeiro, Caroline Madalena; Alcantara, Luciana Leite de Mattos; Souza Júnior, Paulo Roberto Borges de; Szwarcwald, Célia Landmann (Revista de Saúde Pública, 2023)
OBJECTIVES: To compare the coverage of cervical cancer screening in Brazil in 2013 and 2019, investigating the factors associated with having the test performed and the reasons given for not doing it. Additionally, a comparison is made concerning the time taken to receive the test result in SUS (Sistema Único de Saúde) and in the private health services. METHODS: Using data from the National Health Survey (Pesquisa Nacional de Saúde - PNS), prevalence rates and corresponding confidence intervals were calculated to determine the frequency of recent cervical cancer screenings among women aged between 25 and 64 years old in Brazil, for both 2013 and 2019. Poisson regression models were employed to compare the prevalence of the outcome according to sociodemographic characteristics. The reasons for not having the test and the time between performing and receiving the result were also analyzed. RESULTS: The findings revealed an increase in the coverage of preventive cervical cancer exams in Brazil from 78.7% in 2013 to 81.3% in 2019. Additionally, there was a decline in the proportion of women who had never undergone the exam, from 9.7% to 6.1%. Prevalence of test uptake was higher among white women, those with higher levels of education and income, and those residing in the South and Southeast regions of the country. The most commonly cited reasons for not taking the test were the impression it was unnecessary (45% in both 2013 and 2019) and never having been asked to undergo the test (20.6% in 2013 and 14.8% in 2019). CONCLUSIONS: Despite the high coverage of screening achieved in the country, there is great inequality in access to the test, and a non-negligible number of women are at greater risk of dying from a preventable disease. Efforts must be made to structure an organized screening program that identifies and captures the most vulnerable women.